A qualitative process evaluation of a randomised controlled trial of a parenting intervention in community (school) settings for children at risk of attention deficit hyperactivity disorder (ADHD). Issue 1 (December 2015) - Taylor, John; Valentine, Althea; Sellman, Edward; Bransby-Adams, Kate; Daley, David; Sayal, Kapil
Abstract Background Interventions for parents of children experiencing emotional and/or behavioural difficulties can help to improve their children's health, educational and social outcomes. However, the desirability and acceptability of screening and offering such interventions for attention-deficit hyperactivity disorder (ADHD)-type problems are currently unclear. This article is a qualitative process evaluation of a pragmatic cluster randomised controlled trial (Trial registration: ISRCTN87634685; reported elsewhere) to assess the feasibility and acceptability of a school-based parenting intervention programme for parents and teachers of children with high levels of ADHD symptoms. Methods Parents (n = 22) and teaching staff (n = 29) took part in semi-structured group or individual interviews, either by telephone or face-to-face, following the main trial. Interviews were digitally-recorded, transcribed verbatim and subjected to thematic analysis. Results The parenting intervention was acceptable to parents and teachers, and they were enthusiastic about the need for parenting groups in the school environment and stressed the importance of parent-school collaboration. Parents generally stated a preference for universal recruitment approaches to such programmes whilst teachers described the need to target specific parents. Most parents who took part in the parenting intervention described it favourably and many saw benefits, at least in the short-term. Parents differed in their preferred group size, with some desiring one-to-one sessions and others favouring a larger group. Non-attending parents reported barriers to attendance such as fear of attending in a group, previous use of the programme, work and other commitments. Suggestions to improve the programme included: clearer communication; offering booster sessions; and greater collaboration with teachers. Conclusions It is feasible to deliver parenting intervention programmes within or near schools. The intervention was acceptable to the majority of parents, thus retention was high, but recruitment was difficult and reaching the parents with the most need was challenging. The findings of the process evaluation identified greater benefits to families than were apparent in the main trial. Recommendations identified by parents and teaching staff may be used to inform service delivery and future research to enhance recruitment to parenting interventions in the school environment.